Building Pedagogical Synergy in Indonesian Language and Literature Learning in the Principles, Strategies, and Techniques of 21st Century Learning - I Gusti Lanang Agung Pratama Wiguna; I Nyoman Sudiana; Ermalinda Yosefa Awe; M. Zainal Mustamiin; M. Taufik (International Journal of Language and Literature, 2025)
In practice, many learning activities still use a fragmented, teacher-centered approach, thereby limiting students' opportunities to develop critical thinking, collaboration, and multimodal literacy. This study aims to analyze the conceptual framework of pedagogical synergy by integrating learning principles, approaches, strategies, and teaching techniques relevant to 21st-century Indonesian Language and Literature learning. This study used a qualitative design with an integrated literature review method combined with a systematic review and thematic synthesis. The research subjects consisted of 60 scientific articles. Data collection was carried out through documentation and literature searches. The instrument contained indicators of learning principles, learning strategies, teaching techniques, technology integration, and implications for the curriculum. Data analysis was conducted using qualitative content analysis techniques, including coding, thematic categorization, and integrative synthesis of research findings. The results of the study indicate that the effectiveness of Indonesian Language and Literature learning can be improved through a pedagogical synergy integrating the Genre-Based Approach, Communicative Language Teaching, Project-Based Learning, and Technology-Enhanced Language Learning. The conclusions of this study indicate that pedagogical synergy provides a comprehensive conceptual framework for bridging the gap between pedagogical theory and classroom learning practices. The implications of this study emphasize the importance of developing integrative and innovative learning designs by teachers and curriculum developers to strengthen 21st-century competencies.